Chemical Recycling of Expanded Polystyrene Waste: Synthesis of Novel Functional Polystyrene-Hydrazone Surface for Phenol Removal - Ali N. Siyal; Saima Q. Memon; Sajida Parveen; Asma Soomro; Mazhar I. Khaskheli; M. Y. Khuhawar (Journal of Chemistry)
Expanded polystyrene (EPS) waste was chemically recycled to a novel functional polystyrene-hydrazone (PSH) surface by acetylation of polystyrene (PS) and then condensation with phenyl hydrazine. The synthesized surface was characterized by the FT-IR and elemental analysis. Synthesized novel functional PSH surface was successfully applied for the treatment of phenol-contaminated industrial wastewater by solid-phase extraction. Multivariant sorption optimization was achieved by factorial design approach. 99.93% of phenol was removed from aqueous solution. FT-IR study showed the involvement of nitrogen of hydrazone moiety of synthesized surface for the uptake of phenol through the hydrogen bonding.